2013
DOI: 10.1016/j.pain.2012.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Adverse event reporting in randomised controlled trials of neuropathic pain: Considerations for future practice

Abstract: High-quality information on the potential benefit and harm of a drug is required for patients and clinicians to make informed treatment decisions and to enable cost-effectiveness modeling to be undertaken. This systematic review describes the collection and reporting of adverse event data as presented in published clinical trials of neuropathic pain for the evaluation of antidepressant or antiepileptic drugs. A total of 74 studies in 16,323 patients published between 1965 and 2012 were identified, of which 43 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 17 publications
0
53
0
Order By: Relevance
“…Smith et al [29,30] reviewed AE reporting practices across 3 pain journals and concluded that clinical trials of pharmacologic treatments did not adequately report AE information. Cornelius et al [5] reviewed AE reporting for trials examining the analgesic efficacy of antidepressant and antiepileptic medications for neuropathic pain, also finding numerous reporting inadequacies. The results of Smith et al [29,30] and Cornelius et al [5] suggest that, despite the availability of reporting guidelines, AE reporting practices in published clinical trials of pharmacologic pain treatments do not provide adequate harms information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smith et al [29,30] reviewed AE reporting practices across 3 pain journals and concluded that clinical trials of pharmacologic treatments did not adequately report AE information. Cornelius et al [5] reviewed AE reporting for trials examining the analgesic efficacy of antidepressant and antiepileptic medications for neuropathic pain, also finding numerous reporting inadequacies. The results of Smith et al [29,30] and Cornelius et al [5] suggest that, despite the availability of reporting guidelines, AE reporting practices in published clinical trials of pharmacologic pain treatments do not provide adequate harms information.…”
Section: Introductionmentioning
confidence: 99%
“…Cornelius et al [5] reviewed AE reporting for trials examining the analgesic efficacy of antidepressant and antiepileptic medications for neuropathic pain, also finding numerous reporting inadequacies. The results of Smith et al [29,30] and Cornelius et al [5] suggest that, despite the availability of reporting guidelines, AE reporting practices in published clinical trials of pharmacologic pain treatments do not provide adequate harms information. Inadequacies in harms reporting, however, are not limited to investigations of analgesic interventions [25].…”
Section: Introductionmentioning
confidence: 99%
“…Adverse events should be collected within randomized controlled trials (RCTs) as standard; however, they are not consistently reported in findings and publications. Although the Consolidated Standards of Reporting Trials (CONSORT) table outlines the framework for reporting adverse events from clinical trials, the reporting adverse event data in neuropathic pain trials has been described as 'substandard' and 'poor' 43,44 .…”
Section: Approaches To Capture Treatment-related Adverse Eventsmentioning
confidence: 99%
“…First line treatment of neuropathic pain is oral amitriptyline or pregabalin and oral duloxetine for painful diabetic neuropathy according to the guidance of National Institute for Health and Clinical Excellence (NICE) [6]. Insufficient pain relief and intolerable side effects of drugs were experienced in NP patients [7]. Some interventional methods are considered for treatment of NP patients that included in neurosurgical interventions, neural blockade and spinal cord stimulation but the effectiveness of interventional management of NP is also limited [8].…”
Section: Introductionmentioning
confidence: 99%